Examining the Mediating Effects of Organizational Trust on the Relationship between Organizational Justice and Job Attitudes among Correctional Staff - Lambert, Eric G. (The prison journal, 2024)
Drawing from organizational justice theory, this study examined the mediating effects of organizational trust on the association between organizational justice (i.e. in the forms of distributive and procedural justice) and the job attitudes of job satisfaction and organizational commitment in a sample of 220 correctional staff employed full-time at a high-security prison in the U.S. Midwest. Ordinary least squares regression results indicated that participant perceptions of organizational trust fully mediated the association between procedural justice and job satisfaction, but only partially mediated the association between distributive justice and job satisfaction. Further, organizational trust fully mediated the association between both distributive and procedural organizational justice and staff commitment toward the organization.